THE IMPACT OF QUALITY COSTS ON FINANCIAL PERFORMANCE-AN ANALYTICAL STUDY IN THE BUSINESS BAY - Teacher. Saad Sabbar Nasif (Scholars Digest Publishing, 2023)
Objective The research aims to analyze the reality of quality costs and its presentation in one of the Iraqi banks, Al Khaleej Commercial Bank, and measure the impact of quality costs on its banking services. To measure the impact of quality costs on financial performance, the following statistical indicators were used: • A simple linear regression model analysis method using annual quality cost data to measure the impact of each quality cost category in each perspective of the balanced cards. • Multiple linear regression model analysis method to measure the impact of quality costs combined in each perspective of the balanced cards. For the purpose of achieving the research objectives, many methods were relied upon to collect data and information from (books, periodicals, university theses, and bank financial reports) with the use of indicators of the (P-A-F) model, represented by the cost of prevention, the cost of evaluation, and the cost of internal and external failure in measuring the independent variables represented by With the elements of quality costs, and the dependent variables (financial performance), it was measured using balanced cards (financial perspective, operations perspective, customer perspective, and growth and learning perspective). The researcher came up with a set of conclusions, the most important of which is that quality costs are more influential in customer satisfaction and employee satisfaction and less influential in return on investment and work productivity. High evaluation costs are accompanied by an increase in internal failure costs, which indicates a weak distribution of work related to business auditing, whether accounting, administrative, or technical. . The research reached several recommendations, the most important of which are that attention should be directed towards identifying and calculating quality costs, collecting and analyzing data, while setting basic standards for spending on prevention costs in proportion to the importance of each activity, and also working to reduce evaluation costs, identifying the reasons for the high costs of internal failure, and working to address these reasons. By reducing damage to financial forms and documents, monitoring and analyzing the causes of external failure for their negative impact on the bank’s reputation, which is the basic basis for building the bank’s identity and public image in front of customers, and preparing annual or quarterly reports of the quality costs spent and comparing the level of performance achieved by adopting balanced card indicators.
Keywords: quality costs, financial performance.